Hizikia fusiformis fractions successfully improve atopic dermatitis indices in anti-CD3-stimulated splenocytes and 2, 4-dinitrochlorobenzene-treated BALB/c mice. (10th December 2013) - Lee, Kyu Ho; Kim, Hee Jung; Kim, Hae Bok; Kim, Seung Tae; Choi, Young Ri; Seo, Da Woom; Yu, Jung Min; Jang, Su Kil; Kim, Sang Moo; Lee, Do-Ik; Joo, Seong Soo
Abstract: Objectives: In the present study, we aimed to examine whether fractions from an edible sea weed, Hizikia fusiformis, had immunomodulatory effects, particularly an anti-atopic effect, by attenuating the expression of T cell-dependent cytokines using in-vitro and in-vivo animal atopic dermatitis-like models. Methods: The anti-atopic activities were examined in in vitro, and a 2, 4-dinitrochlorobenzene (DNCB)-induced atopic dermatitis-like mouse model using quantitative real-time polymerase chain reaction, electrophoretic-mobility shift and histophathological analysis. Key findings: Our results showed that the final fraction (F2′) of H. fusiformis contained a higher amount of butanoic acid which was not found in the other fractions, and effectively inhibited T cell activation by inhibiting dephosphorylation of nuclear factor of activated T cells in electrophoretic-mobility shift assay. As a consequence, helper T cell-dependent cytokines, such as interleukin-2, -4 and interferon-γ, were significantly inhibited while activated with an anti-CD3 antibody. We also showed that skin challenged with DNCB successfully recovered when treated with 2.5 mg/kg, comparable to that by 0.25% prednicarbate. These results indicate that F2′ may contribute to inhibit T cell activation by eliminating Th cell-dependent cytokines. Conclusions: Taken together, we concluded that F2′ containing butanoic acid may be a new functional anti-atopic candidate, which probably acts through nuclear factor of activated T cell inactivation mechanisms.